PENDIDIKAN BERBASIS KEARIFAN LOKAL UNTUK MEMBANGUN INSAN KAMIL - Suryanti, Irmi; Hisri, Tita Bela (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The purpose of this research is to produce teaching materials in local content subjects. There are 4 steps in the preparation of teaching materials that are: 1.Identifikasi requirement, 2. Preparation of syllabus, 3. Production of teaching materials, 4. Evaluation of teaching materials. Research results that existing folklore in Bengkulu province still exist that has not been opened and still scattered diwilah Bengkulu province. From the analysis found good characters found, for example: religious, hardworking , democratic, tolerant, respectful, caring, peaceful, and responsible. And there are also bad characters that are cruel, cunning, miserly and evil. In local content subjects there are some subjects that are taught ie English, regional languages, regional songs, and agriculture. In utilizing folklore in teaching materials is local content using local language in the form of writing language that is Rejang language (Ka Ga Nga). But the use of teaching materials has not come to the character analysis of characters in the story. So that the use of folklore in teaching materials on local content subjects can not be applied maximally. Key words— local content, characters, teaching materials, folklore